STATUS GIZI TIDAK SIGNIFIKAN MENENTUKAN PRESTASI BELAJAR SISWA SD - Vista, Dian; Delima E, Rosa; Hutasoit, Masta (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background : The low Human Development Index (HDI) ranking in Indonesia compared with  neighboring countries affected by the low nutritional status and health problems of Indonesia?a population factor. One of the factor?s facing the health problem?s of Indonesian society is the problem of nutrition, undertrition and obessitas. They both have a negative impact on the quality of health. Government?s efforts to improve nutrition in school children by providing the Food Supplement Program School Children (PMT-AS). Good nutritional status is necessary for physical growth, brain development, employability and optimal health. Abnormalities that occur in the brain due to malnutritional have one impact is the decline  in brain function that affects the ability to learn, resulting in lower children?s learning outcome. Objective : To determine the relationship of nutritional status and student achievement in elementary school Bangunjiwo Kasihan Bantul Yogyakarta. Methods : This study used non-experimental research methods with cross sectional approach. The population in this study were student in grade 6 in SD Negeri Bangunjiwo Kasihan Bantul. The samples used were 43 students. Engineering samples of the total sampling obtained a total sample of 43 students and analize using Spearman. Results : Nutritional status in elementary school Bangunjiwo Kasihan Bantul there are 36 students (83,7%) in the normal category of 43 respondents. A grade students achievement 6 in SD Negeri Bangunjiwo Kasihan Bantul most in categories as many 28 students (65,1%) of the 43 respondent. Conclusion : There was no significant association between nutritional status of student performance, with a value of (p>0,05). Key words : Nutritional status, Learning achievement